Reimagining capitalism in a world on fire : how business can save the world / Rebecca Henderson. - Henderson, Rebecca (Penguin Business, 2021)
Free market capitalism is one of humanity's greatest inventions, and the greatest source of prosperity the world has ever seen. But it's also on the verge of destroying the planet and destabilizing society in its single-minded pursuit of maximizing shareholder value. Rebecca Henderson, McArthur University Professor at Harvard University, argues for a new framework; one that can simultaneously make a positive societal impact by confronting the realities of the environment and the need to address social and economic inequality, while also delivering sustained financial performance to ensure economic growth that brings prosperity and wellbeing to society as a whole.